Effect of Acarbose on High Carohydrate Diet Induced Liver Injury in Largemouth Bass (Micropterus salmoides) - Yanhao CAO; Xiaolong BO; Hongli LIU; Xiaoli HUANG (Guangdong nongye kexue)
【Objective】The study was conducted to investigate the effect of acarbose on high-carbohydrate dietinduced liver injury in largemouth bass and to detect similar functional therapeutic drugs in the initial screening.【Method】The largemouth bass (Micropterus salmoides) with an initial body weight of 7.25 (±1.67) g was taken as research object. First, a normal-level carbohydrate group (1.3% α-starch, CK) and a high carbohydrate group (22.0% α-starch, high carbohydrate group) were set up to induce high carbohydrate diet-induced liver injury. Then, largemouth bass with an initial body weight of 7.5 mg/kg was fed with acarbose to explore the therapeutic effects of acarbose on high carbohydrate diet-induced liver injury by using gross pathology, histopathology, enzymology, and flow cytometry. In addition, six candidate Chinese herbal medicines were screened by simulating the sugar control principle of acarbose, and their therapeutic effects on high carbohydrate dietinduced liver injury were preliminarily analyzed.【Result】Continuous feeding of high carbohydrates for 45 days could cause liver enlargement, whitening, and a significant increase in liver to body ratio in largemouth bass (P < 0.05). After 15 days of treatment with acarbose, compared with the high carbohydrate group, the blood glucose level of largemouth bass decreased by 1.77 mol/L, ALT and AST activities decreased to 42.00 U/L and 157.67 U/L, respectively, while ALKP activity increased and showed a trend of returning to normal values, effectively slowing down hepatocyte vacuolization and reducing hepatic glycogen accumulation. The results of flow cytometry showed that the total apoptosis rate of liver cells in the high carbohydrate group was the highest at 4.64% among the three groups, while that of the acarbose group significantly decreased to 1.24% (P < 0.05). In addition, compared with the control group, the ROS content in the liver tissue of largemouth bass in the high carbohydrate group increased to 30.94%, while that decreased to 22.35% in the acarbose group, showing a trend of returning to normal levels. After 15 days of treatment with 6 types of Chinese herbal medicine, the liver morphology was maintained and the liver to body ratio was reduced, however, there was no significant difference among different treatments (P > 0.05). Among them, cinnamon treatment had a more significant effect, reaching the lowest liver to body ratio at 3.35%.【Conclusion】Acarbose can effectively alleviate liver enlargement in largemouth bass caused by high carbohydrate diets, reduce liver to body ratio, alleviate liver cell apoptosis and vacuolization, reduce liver glycogen accumulation, alleviate oxidative stress damage in the body, thus protect the health of largemouth bass. Among the six traditional Chinese medicines, cinnamon has a better therapeutic effect and has a similar effect to acarbose. It can be used as a candidate herbal medicine for further development and utilization to treat high carbohydrate diet-induced liver injury in largemouth bass.